2010
DOI: 10.3109/03093641003776976
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Prosthetic Outcome Measures

Abstract: The International Classification of Functioning, Disability and Health (ICF) has been recommended as a framework for evaluation of aspects of health. The aim of this study was to compare the contents of outcome measures for upper limb prosthesis users by using the ICF. Measurement focus and psychometric properties of these measures were also investigated. Outcome measures that used upper limb prosthesis users as subjects in their development and psychometric evaluations were selected. The psychometric studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 54 publications
(142 reference statements)
0
47
0
Order By: Relevance
“…As such, we follow and extend the suggestion put forth in several recent articles that evaluated measures of prosthesis functioning at the clinical level [1,[3][4]. In these articles, it was concluded that several outcome measures should be combined to provide a complete picture of the functional ability of a prosthesis user instead of using only one outcome measure.…”
Section: Introductionmentioning
confidence: 59%
“…As such, we follow and extend the suggestion put forth in several recent articles that evaluated measures of prosthesis functioning at the clinical level [1,[3][4]. In these articles, it was concluded that several outcome measures should be combined to provide a complete picture of the functional ability of a prosthesis user instead of using only one outcome measure.…”
Section: Introductionmentioning
confidence: 59%
“…Different instruments have been used to measure functional outcomes in users of upper-limb prostheses [5][6][7]. Although some of them have been used for many years in clinical practice, their validity evidence for the upper-limb prosthetic group has not been fully investigated [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Kohler et al 16 wrote about core set development for people following amputation and two studies linked outcome measures to ICF. 5,6 Raggi et al 24 found the WHO-DAS II, an ICF-based disability instrument to be sensitive to the influence of assistive technology on person's functioning, but none of the included subjects had a prosthesis or orthosis.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all these outcome measures were developed before the publication of the International Classification of Functioning, Disability and Health (ICF) 4 and most of them do not cover the full spectrum of human functioning. 5,6 The main goal of prostheses and orthoses is to improve individual functioning. Prostheses replace an amputated part of the body and try to restore the lost body function and decrease the problems with activities and participation.…”
Section: Introductionmentioning
confidence: 99%